DYSPHEMISM IN THE YOUTUBE COMMENTS SECTION: INSIGHTS FROM NIKOCADO AVOCADOâ€™S â€œTWO STEP AHEADâ€ VIDEO - Oktaviana, Dina; Bowo, Tri Arie; Sigalingging, Bob Morison (Universitas Muhammadiyah Lampung, 2025)
The study of dysphemism remains significant because it is frequently observed in daily interactions as a way to express strong emotions such as anger, frustration, or dislike, both on direct conversations, and digital platforms. This study examines the types and effects of dysphemism in YouTube comments in the video â€œTwo Steps Aheadâ€ by Avocado Nicokado. This study uses a qualitative descriptive method, the research identifies dysphemisms based on Allan and Burridgeâ€™s (2006) framework. To collect the data, the researcher accessed the Nikocado Avocado YouTube channel and selected the video â€œTwo Step Ahead,â€ which had 49 million views and 304,726 comments. The 25 comments were analyzed as data, with relevant ones captured using screenshots and notes, and the identified dysphemistic terms were cross-checked for accuracy. Based on 25 analyzed comments, 31 dysphemistic words and phrases were identified. The data revealed the following types of dysphemism: 9 are categorized as taboo terms, 4 as profane swearing and oaths, 1 as comparisons with animals, 1 as dysphemistic epithets, 7 as imprecations and epithets, 1 as -IST dysphemism, and 8 as terms of insult. Based on the data, taboo words and phrases were the most frequent, followed by insult terms and imprecations and epithets, mostly used to insult and mock Nikocado, though some expressed shock and admiration. Dysphemism can affect people's perspectives. It also provides emotional release, affecting how individuals express frustration or surprise. While generally negative, dysphemism can create closeness in informal contexts but may also deepen polarization and reinforce existing biases.